Clinical opportunities in combining immunotherapy with radiation therapy - Finkelstein, Steven E.; Fishman, Mayer (Frontiers in Oncology, 2012)
Preclinical work in murine models suggests that local radiotherapy plus intratumoral syngeneic DC injection can mediate immunologic tumor eradication. Radiotherapy affects the immune response to cancer, besides the direct impact on the tumor cells, and other ways to coordinate immune modulation with radiotherapy have been explored. We review here the potential for immune mediated anticancer activity of radiation on tumors. This is mediated by antigen acquisition and presentation by dendritic cells, and through changes of lymphocytes’ activity. Recent work has implemented the combination of external beam radiation (EBRT) with intratumoral injection of dendritic cells (DC). This included a pilot study of coordinated intraprostatic, autologous DC injection together with radiation therapy with five HLA-A2(+) subjects with high-risk, localized prostate cancer; the protocol used androgen suppression, external beam radiation therapy (25 fractions, 45 Gy), DC injections after fractions 5, 15, and 25, and then interstitial radioactive implant. Another was a phase II trial using neo-adjuvant cell death-inducing EBRT plus intra-tumoral DC in soft tissue sarcoma, to test if this would increase immune activity toward soft tissue sarcoma associated antigens. Clinical experience using radiation therapies combined with other systemic immune treatments are additionally surveyed, including use of investigational recombinant vaccinia and fowlpox, interleukin-2, toll like receptor 9 (TLR9) agonists and lymphocyte checkpoint inhibitors directed at PD1 and at CTLA4.